Influence of chemical composition and holding time on austenite (γ) → ferrite (α) transformation in ductile iron occurring within the intercritical interval - Basso, Alejandro Daniel (2011)
This work focuses on the influence exerted by the chemical composition on the characteristics of the γ → α reaction occurring within the intercritical interval of the Fe-C-Si diagram, in order to produce a new "dual phase ADI" variant. Three ductile iron melts with different chemical compositions were used and several thermal cycles were performed. The results show a strong dependence between the alloy composition and the characteristics of the γ → α reaction, affecting the amount as well as the morphology of the precipitated allotriomorphic ferrite. Low alloy content promotes ferritic nucleation around graphite nodules and fast growth. Moreover, when the alloy content increases, the ferrite nucleates preferentially at the grain boundaries of the recrystallized austenite, and grows very slowly forming a continuous net. This novel microstructure is expected to enhance the mechanical properties of ductile cast iron. © 2011 Elsevier B.V.